How threatened are plants?: assessing conservation status of plants to support global conservation targets - Bachman, Steven P. (2019)
This thesis aims to gain a more quantitative answer to the question: ‘How threatened are plants?’ Plants make up a large component of the world’s biota but are suffering as a result of pressures from anthropogenic activities including land cover change, over-consumption of plant resources and stresses associated with a changing climate. Loss of plants, either in terms of reduction in abundance or in the extreme case, extinction of species, will reduce the stability of ecosystems, and will potentially cause the collapse of ecosystems. Insufficient resources are available to protect all plants and a process of prioritisation is therefore needed to stem the losses resulting from anthropogenic activities.